2005
DOI: 10.3988/jcn.2005.1.1.31
|View full text |Cite
|
Sign up to set email alerts
|

New England Medical Center Posterior Circulation Stroke Registry II. Vascular Lesions

Abstract: Among 407 New England Medical Center Posterior Circulation Registry (NEMC-PCR) patients, the extracranial (ECVA) and intracranial vertebral arteries (ICVA) were the commonest sites of severe occlusive disease followed by the basilar artery (BA). Severe occlusive lesions were found in >1 large artery in 148 patients; 134 had unilateral or bilateral severe disease at one arterial location. Single arterial site occlusive disease occurred most often in the ECVA (52 patients, 15 bilateral) followed by the ICVA (40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 91 publications
(126 reference statements)
4
75
0
3
Order By: Relevance
“…This was comparable with study by Caplan et al where hypertension was risk factor in 61% patients. 15 Other risk factors found by them were tobacco abuse (35%), diabetes (25%) and dyslipidaemia (25%). Kora et al found most common risk factor for posterior circulation stroke as tobacco abuse 52% and hypertension as the second common risk factor (37%).…”
Section: Resultsmentioning
confidence: 99%
“…This was comparable with study by Caplan et al where hypertension was risk factor in 61% patients. 15 Other risk factors found by them were tobacco abuse (35%), diabetes (25%) and dyslipidaemia (25%). Kora et al found most common risk factor for posterior circulation stroke as tobacco abuse 52% and hypertension as the second common risk factor (37%).…”
Section: Resultsmentioning
confidence: 99%
“…Various transitory premonitory neurological symptoms, mainly from dysfunction of vestibulocerebellar (dizziness and vertigo) or motor/oculomotor brain stem structures (dysarthria), were reported in 79% of our patients and a slightly lower frequency (64%) was also noted in the group of patients with severe bilateral ICVA occlusive disease [15]. The majority of our subjects had documented or self-reported vertebrobasilar TIAs in the last 36 h preceding stroke, but this could be to some extent the result of recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, Patterson and Grabois [3] reported that the majority of patients with ischemic LIS also had TIAs during the day prior to the onset of stroke. The data from NEMC-PCR study show that the average period of time during which TIAs occurred in patients with bilateral pontine infarctions due to BA thrombosis is much shorter than in those with extensive posterior circulation disease (mean 2.1 vs. 7.8 months) [15]. This narrow time window, between multifocal vertebrobasilar TIAs and an impending acute BA occlusion possibly resulting in a locked-in state, highlights the need for urgent neurovascular evaluation in patients with clinical signs of severe BA occlusive disease [16].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Outcomes also could be analyzed in relation to brain location, vascular lesions, and stroke mechanisms. 20 Because designation of stroke mechanism was controversial in the Harvard Stroke Registry and the Stroke Data Bank, we chose a different strategy in the NEMC-PCR.…”
Section: New England Medical Center Posterior Circulation Registry 17-25mentioning
confidence: 99%